Chaotic oceanic excitation of low-frequency polar motion variability - L. Börger; M. Schindelegger; M. Zhao; R. M. Ponte; A. Löcher; B. Uebbing; J.-M. Molines; T. Penduff (Earth System Dynamics)
Studies of Earth rotation variations generally assume that changes in non-tidal oceanic angular momentum (OAM) manifest the ocean's direct response to atmospheric forces. However, fluctuations in OAM may also arise from chaotic intrinsic ocean processes that originate in local nonlinear (e.g., mesoscale) dynamics and can map into motions and mass variations at basin scales. To examine whether such random mass redistributions effectively excite polar motion, we compute monthly OAM anomalies from a 50-member ensemble of eddy-permitting global ocean/sea ice simulations that sample intrinsic variability through a perturbation approach on model initial conditions. The resulting OAM (i.e., excitation) functions, <mover accent="true">χ^</mover>O<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="16pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="4209a2ebd874764d16b60e77545a25e3"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="esd-16-75-2025-ie00001.svg" width="16pt" height="15pt" src="esd-16-75-2025-ie00001.png"/></svg:svg>, are examined for their spread, spectral content, and role in the polar motion excitation budget from 1995 to 2015. We find that intrinsic <mover accent="true">χ^</mover>O<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="16pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="5a07498b9a02c6f507300fc609dd0ab6"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="esd-16-75-2025-ie00002.svg" width="16pt" height="15pt" src="esd-16-75-2025-ie00002.png"/></svg:svg> signals are comparable in magnitude to the forced component at all resolved periods except the seasonal band, amounting to ∼ 46 % of the total oceanic excitation (in terms of standard deviation) on interannual timescales. More than half of the variance in the intrinsic mass term contribution to <mover accent="true">χ^</mover>O<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="16pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="b692688346d4fcfacee2f6152b71e819"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="esd-16-75-2025-ie00003.svg" width="16pt" height="15pt" src="esd-16-75-2025-ie00003.png"/></svg:svg> is associated with a single global mode of random bottom pressure variability, likely generated by nonlinear dynamics in the Drake Passage. Comparisons of observed interannual polar motion excitation against the sum of known surficial mass redistribution effects are sensitive to the representation of intrinsic <mover accent="true">χ^</mover>O<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="16pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="0f3a73f3fbed0a489e998628e7d4569c"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="esd-16-75-2025-ie00004.svg" width="16pt" height="15pt" src="esd-16-75-2025-ie00004.png"/></svg:svg> signals: reductions in the observed excitation variance can be as high as 68 % or as low as 50 % depending on the choice of the ensemble member. Chaotic oceanic excitation thus emerges as a new factor to consider when interpreting low-frequency polar motion changes in terms of core–mantle interactions or employing forward-modeled OAM estimates for Earth rotation predictions.